MEDIASI SEBAGAI PENYELESAIAN PERMASALAHAN TENAGA KERJA DI KABUPATEN BANGKALAN - Abd Latip; Lu’luiaily Lu’luiaily; Ainiyah Ainiyah (Kompetensi (Competence : Journal of Management Studies), 2018)
ABSTRACT The relationship between workers and employers does not always run smoothly, there are times when one or both parties neglect their obligations or do not fulfill their rights. With the non-fulfillment of these rights or obligations, it can lead to industrial relations disputes between workers and employers. Appropriate disputes can be resolved between each party through Bipartite which is carried out by the Bangkalan City Manpower Office based on deliberation and consensus and will result in a joint agreement between the two parties. But often with this agreement no agreement was reached, so that the dispute issue was resolved in a tripartite manner through mediation, conciliation, arbitration. The problem in this article is how the implementing regulations are in resolving industrial relations disputes and what are the driving and inhibiting factors in the effectiveness of work relations in resolving industrial relations disputes.